Roman oil lamps with peltae relief on base. New evidence from Apsaros (Gonio, Georgia) - Jaworska, Maria (Studia Europaea Gnesnensia, 2020)
Discovery of two lamps at the Roman fort of Apsaros (Gonio, Georgia) offers further insights concerning adaptation of the pelta motif on Roman lamps. Inquiry into the nature of the ornaments on the base – previously unknown in Colchis – leads to conclusions about the possible influx of goods to the fort located on the outskirts of the Roman Empire.